Selection of Appropriate Wound Dressing for Various Wounds - Shi, Chenyu; Wang, Chenyu; Liu, He; Li, Qiuju; Li, Ronghang; Zhang, Yan; Liu, Yuzhe; Shao, Ying; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2020)
There are many factors involved in wound healing, and the healing process is not static. The therapeutic effect of modern wound dressings in the clinical management of wounds is documented. However, there are few reports regarding the reasonable selection of dressings for certain types of wounds in the clinic. In this article, we retrospect the history of wound dressing development and the classification of modern wound dressings. In addition, the pros and cons of mainstream modern wound dressings for the healing of different wounds, such as diabetic foot ulcers, pressure ulcers, burns and scalds, and chronic leg ulcers, as well as the physiological mechanisms involved in wound healing are summarized. This article provides a clinical guideline for selecting suitable wound dressings according to the types of wounds.